2014
DOI: 10.1097/pai.0b013e3182936ea7
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Utility of PLAG1 Immunohistochemical Determination in Salivary Gland Tumors

Abstract: PLAG1 (pleomorphic adenoma gene 1) is a proto-oncogene whose overexpression is a crucial oncogenic event in salivary gland pleomorphic adenomas (PA), and in carcinoma ex-PA. The aim of the present study is to evaluate the sensitivity and the specificity of PLAG1 as a marker in the differential diagnosis of salivary gland benign and malignant tumors. We examined 101 cases, including 36 PAs, 8 myoepitheliomas, 3 basal cell adenomas, and 1 canalicular adenoma among benign tumors; 16 mucoepidermoid carcinomas, 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 9 publications
4
59
0
Order By: Relevance
“…In their study of 101 cases of salivary gland lesions including 36 PAs, Rotellini et al [6] observed diffuse PLAG1 positivity in 94.4% of the PAs, which is comparable to the results in our cases of PA SE specimens. None of the BCAs in their cases were positive for PLAG1.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In their study of 101 cases of salivary gland lesions including 36 PAs, Rotellini et al [6] observed diffuse PLAG1 positivity in 94.4% of the PAs, which is comparable to the results in our cases of PA SE specimens. None of the BCAs in their cases were positive for PLAG1.…”
Section: Discussionsupporting
confidence: 80%
“…The transcriptional upregulation of PLAG1 leads to a high level of protein expression in PAs with PLAG1 rearrangements [4,5]. A few studies have analyzed the utility of PLAG1 in salivary gland neoplasms [6,7,8], but these have mostly been on surgical excision (SE) specimens. FNA materials present a diagnostically unique challenge because of the limited material on which the diagnosis is made.…”
Section: Introductionmentioning
confidence: 99%
“…2b), but is negative in myoepitheliomas lacking ductal differentiation [16]. Similarly, the majority of salivary pleomorphic adenomas are positive for PLAG1 [17,18] and frequent positivity is observed in 77 % of carcinomas ex pleomorphic adenoma in salivary gland, including those classified as the myoepithelial carcinoma subtype [19].…”
Section: Immunohistochemical Featuresmentioning
confidence: 97%
“…Periodic acid Schiff (PAS) with and without diastase, A review of publications in English (MEDLINE 1966-2014) was performed, with all cases reported with clinical, histologic, immunophenotypic and/or follow-up information on CanAd evaluated and included in the review, but excluding ''Quiz'' or ''Case of the Month'' type reports. Several studies were excluded if no specific or separable information was given about CanAd or if the illustrations were not characteristic [23,51,55,[59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78]. Several of the cases seemed to have been included multiple times in different series reports [9,10,40,[79][80][81][82][83].…”
Section: Methodsmentioning
confidence: 99%